Regulating access to the fiber in Turkey: Would regulatory holiday be a tool to increase the investment of operators? - Mehmet Bilal Ünver; Erhan İlhan (International Telecommunications Society (ITS), 2013)
In this paper, regulatory policies and their effects on NGA investment are analysed through a categorisation of four-part: (i) conventional (e.g., copper-based) type regulation, (ii) no imposition of mandatory access, (iii) regulatory holiday, (iv) deregulation. While EU's regulatory policy towards NGA networks originally was denoting somewhere between the first two options, the recent developments refashion an approach near the first. While US experience clearly exhibits deregulation under the fourth category, Turkey's NGA policy repsesents an approach near the third yet marking a difference with the regulatory steps taken recently. This study first elaborates Turkish experience, then deepens EU regulatory approach from the beginning to the its current NGA strategy under the recommended principles and Commission's decisional practice. Throughout the discussion, the interplay beween copper based regulations, e.g., LLU prices and the NGA investments are delved into with factual analysis along with the market behaviours. At last, it is found that conventional regulatory approach has hazardopus effects over NGA investment, and needs to be overhauled in view of some tools that could be gained from Turkish experience, e.g., protecting first-mover advantages from regulation along with ascertained rules of level playing field. Last but not the least, rather than US based deregulation, a controlled regulatory holiday would rather be an appropriate option given the need for regulatory predictability and the hazards of conventional regulatory approach in an emerging NGA environment.
Keywords: 330